Social Integration of the Former Transcarpathian Students of the Balassi Institute - Pallay, Katalin (Central European Journal of Educational Research, 2020)
In the present study, we examine the social integration of former Transcarpathian students who participated in the university preparatory training of the Balassi Institute. Social integration plays a major role, both among mobile students settling in the destination country and in the sending country. Despite the fact that Hungarian students from Transcarpathia have the same linguistic and cultural background as their motherland, their integration into Hungarian society is often hampered: migration often involves giving up home connections, and the success of building new ones is unpredictable. Successful adaptation to the social environment of the destination country is not always an automatic mechanism. Our research was conducted using a questionnaire method. In the survey, we sought to answer the question of where the former Transcarpathian students participating in the preparatory training of the Balassi Institute settled after completing their studies and how they managed to integrate into the society of their place of residence. We compare the social integration of people returning to Transcarpathia, settling in Hungary and living abroad. In summary, we would like to present the results of the survey.